Does Education Enhance Entrepreneurship? - Kunwon Ahn; John V. Winters (Institute of Labor Economics (IZA), 2021)
Formal education is correlated with entrepreneurial activity and success, but correlation does not indicate causation. Education and entrepreneurship are both influenced by other related factors. The current study estimates causal effects of formal education on entrepreneurship outcomes by instrumenting for an individual's years of schooling using cohort mean years of maternal schooling observed decades prior. We differentiate self-employment by industry employment growth and firm incorporation status. We have multiple important results. Formal schooling significantly increases the probability of self-employment in high-growth industries for both women and men. Education reduces the probability of male self-employment in shrinking industries. Education also increases incorporated self-employment for women and men and reduces unincorporated self-employment among men but not women. The overall probability of self-employment increases with education for women but is unaffected by education for men. The results suggest that formal education enhances entrepreneurship.
Keywords: I20; J24; L26; 330; entrepreneurship; self-employment; education; human capital